Laying Eggs in Others’ Nests: The Need for Recognition of Co-authorship in Copyright Law from a Sri Lankan and European Perspective - Punchihewa, N.S. (University of Colombo, 2024)
The issue of recognizing co-authorship in a work has created a considerable tension in Sri Lanka and Europe. The legal questions raised in the German and French cases of Kippernberger and Druet respectively offer new significant insights into analysing the recent decision issued by the Supreme Court of Sri Lanka in Dharma Samaranayake v Sarasavi Publishers. Copyright law aims to protect the rights of the individual authors. The works of joint authorship or co-authorship are recognized under the Sri Lankan as well as European copyright law. Therefore, the purpose of this paper is to explore what criteria can be effectively used to establish the co-authorship in a copyrightable work. While the European authors’ right regime requires a work to reflect the personality of the author, the common law copyright system applies the skill, labour, and judgement doctrine. In terms of the methodological approach, this research dwells within the positivist black-letter legal research methodology coupled with comparative legal analysis. The results of this research indicate that Kippernberger and Druet cases shed significant light on the principal question raised in the Dharma Samaranayake case. Even though no arguments had been made in favour of establishing the co-authorship rights in the said Sri Lankan case, it is clear that a different outcome could have been reached had that the particular argument been taken up by the parties. Therefore, the decisive factor should be “who holds the creative control of the work.” It is evident that both the author mentioned in the book and editor who claimed the authorship ...
Keywords: Copyright; Co-authorship; Creative Control; Fair Crediting